The Role of Green Innovation to Achieve Sustainable Business Performance of MSMEs in the Covid-19 Pandemic - Sisca, Sisca; Wijaya, Andy (Publisher Cv. Inara, 2023)
The Covid-19 pandemic has had a major impact on economic growth in Indonesia, one of which is for Micro, Small and Medium Enterprises (MSMEs). Thus, MSMEs need to improve their business performance in a sustainable manner to achieve the desired economic growth, one of which is through the adoption of green innovation. The purpose of this study was to analyze the relationship between the adoption of green innovation and sustainable business performance of MSMEs especially during the Covid-19 Pandemic. The research subjects taken in this study were MSME actors in the food and beverage sector at Pematangsiantar City, totaling 371 MSMEs. The analysis technique used in this study was Structural Equation Modeling (SEM) using the Smart PLS program. The results of this study indicated that green innovation has a positive and significant influence on sustainable business performance, especially on social performance and environmental performance, while it has no significant effect on economic performance.